Deucravacitinib, a tyrosine kinase 2 pseudokinase inhibitor, protects human EndoC-βH1 β-cells against proinflammatory insults - Dos Santos, Reinaldo S.; Guzman-Llorens, Daniel; Perez-Serna, Atenea A.; Nadal, Angel; Marroqui, Laura (Frontiers in Immunology, 2023)
Type 1 diabetes is characterized by pancreatic islet inflammation and autoimmune-driven pancreatic b-cell destruction. Interferon-α (IFNα) is a key player in early human type 1 diabetes pathogenesis. IFNα activates the tyrosine kinase 2 (TYK2)-signal transducer and activator of transcription (STAT) pathway, leading to inflammation, HLA class I overexpression, endoplasmic reticulum (ER) stress, and b-cell apoptosis (in synergy with IL-1β). As TYK2 inhibition has raised as a potential therapeutic target for the prevention or treatment of type 1 diabetes, we investigated whether the selective TYK2 inhibitor deucravacitinib could protect b-cells from the effects of IFNα and other proinflammatory cytokines (i.e., IFNγ and IL-1β). All experiments were performed in the human EndoC-βH1 β-cell line. Inflammation, ER stress, and apoptosis were evaluated by real-time PCR, immunoblot, immunofluorescence, and nuclear dyes. The promoter activity was assessed by luciferase assay. Deucravacitinib prevented IFNα effects, such as STAT1 and STAT2 activation and MHC class I hyperexpression, in a dose-dependent manner without affecting b-cell survival and function. A comparison between deucravacitinib and two Janus kinase inhibitors, ruxolitinib and baricitinib, showed that deucravacitinib blocked IFNα-but not IFNγ-induced signaling pathway. Deucravacitinib protected b-cells from the effects of two different combinations of cytokines: IFNα + IL-1β and IFNγ + IL-1β. Moreover, this TYK2 inhibitor could partially reduce apoptosis and inflammation in cells pre-treated with IFNα + IL-1β or IFNγ + IL-1β. Our findings suggest that deucravacitinib could be repurposed for the prevention or treatment of early type 1 diabetes.